2003
DOI: 10.1073/pnas.242720499
|View full text |Cite
|
Sign up to set email alerts
|

Chaperones increase association of tau protein with microtubules

Abstract: Molecular chaperones and their functions in protein folding have been implicated in several neurodegenerative diseases, includingParkinson's disease and Huntington's disease, which are characterized by accumulation of protein aggregates (e.g., ␣-synuclein and huntingtin, respectively). These aggregates have been shown in various experimental systems to respond to changes in levels of molecular chaperones suggesting the possibility of therapeutic intervention and a role for chaperones in disease pathogenesis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
407
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(428 citation statements)
references
References 45 publications
(38 reference statements)
18
407
2
1
Order By: Relevance
“…This function is accomplished due to the proteins' intracellular chaperone activity and is responsible for the refolding of stressdenatured proteins and stabilization of transcription and translation (Lindquist and Craig 1988;Morimoto 1991;De Maio 1999). More recently, it has been shown that hsp also regulate other cellular activities such as cytoskeleton rearrangement (Han et al 2000;Kirby et al 1994;Liao et al 1995;Dou et al 2003;Lavoie et al 1993;Piotrowicz and Levin 1997), endocytosis and phagocytosis (Vega et al 2010;Vega and De Maio 2005), and activation of immune cells (Vega et al 2008;Asea et al 2000Asea et al , 2002. Especially interesting is the capacity of both extra-and intracellular hsp to regulate the immune system by activation of key cells such as macrophages (Mfs) and dendritic cells, thereby controlling inflammatory and immune responses (Vega et al 2010;De Maio 2010;Asea et al 2000Asea et al , 2002Basu et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This function is accomplished due to the proteins' intracellular chaperone activity and is responsible for the refolding of stressdenatured proteins and stabilization of transcription and translation (Lindquist and Craig 1988;Morimoto 1991;De Maio 1999). More recently, it has been shown that hsp also regulate other cellular activities such as cytoskeleton rearrangement (Han et al 2000;Kirby et al 1994;Liao et al 1995;Dou et al 2003;Lavoie et al 1993;Piotrowicz and Levin 1997), endocytosis and phagocytosis (Vega et al 2010;Vega and De Maio 2005), and activation of immune cells (Vega et al 2008;Asea et al 2000Asea et al , 2002. Especially interesting is the capacity of both extra-and intracellular hsp to regulate the immune system by activation of key cells such as macrophages (Mfs) and dendritic cells, thereby controlling inflammatory and immune responses (Vega et al 2010;De Maio 2010;Asea et al 2000Asea et al , 2002Basu et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to co-express gene products with the vector system permits screening gene targets that can either intensify tau pathology or block it. For example, chaperone co-factors such as Hsp70 can regulate tau processing (Dou et al, 2003;Petrucelli et al, 2004). If a specific gene product efficaciously blocks tau toxicity in rats, it could be pursued as a gene therapy for tauopathies, especially genetically determined tauopathies such as FTDP-17, because there are no treatments currently available for this fatal condition.…”
Section: Discussionmentioning
confidence: 99%
“…35 Cells were lysed in a buffer containing 0.5% Nonidet P-40, 1 mM EDTA, 50 mM Tris-HCl, pH 8.0, 120 mM NaCl, and a protease inhibitor mixture. After brief sonication, cell lysates were passed through a cellulose acetate membrane (0.2 mm; Bio-Rad) using a Bio-Dot Microfiltration Apparatus (Bio-Rad) and were washed for 15 min (three times) with 1% SDS followed by immunoblotting using Tau5 antibody.…”
Section: Filter/trap Assays For Tau Aggregatesmentioning
confidence: 99%